2021
DOI: 10.3390/plants10122664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics, Evolution, and Drought-Induced Expression of Dehydrin Genes in Model Brachypodium Grasses

Abstract: Dehydration proteins (dehydrins, DHNs) confer tolerance to water-stress deficit in plants. We performed a comparative genomics and evolutionary study of DHN genes in four model Brachypodium grass species. Due to limited knowledge on dehydrin expression under water deprivation stress in Brachypodium, we also performed a drought-induced gene expression analysis in 32 ecotypes of the genus’ flagship species B. distachyon showing different hydric requirements. Genomic sequence analysis detected 10 types of dehydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
(154 reference statements)
0
19
0
Order By: Relevance
“…This aligned with a niche competition hypothesis [33] that suggests the favouring of the newly formed allotetraploids in non-native habitats. Nonetheless, population analyses indicate that climate niche parameters and functional and phenotypic eco-physiological responses to environmental stress are more genotype-dependent within each species [32,34,35]. Phylogenomics of the pangenome has revealed up to five highly divergent Mediterranean lineages, which split from the common ancestor 0.16 Ma [27,36,37], showing some signs of geographic structure coupled with frequent long-distance dispersals.…”
Section: Trends Trends In In Plant Plant Science Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…This aligned with a niche competition hypothesis [33] that suggests the favouring of the newly formed allotetraploids in non-native habitats. Nonetheless, population analyses indicate that climate niche parameters and functional and phenotypic eco-physiological responses to environmental stress are more genotype-dependent within each species [32,34,35]. Phylogenomics of the pangenome has revealed up to five highly divergent Mediterranean lineages, which split from the common ancestor 0.16 Ma [27,36,37], showing some signs of geographic structure coupled with frequent long-distance dispersals.…”
Section: Trends Trends In In Plant Plant Science Sciencementioning
confidence: 99%
“…Nonetheless, the extraordinary natural diversity of B. distachyon and its robust pangenome has served to launch a variety of studies into the sources of variation. These include potential interlineage isolation caused by different flowering times [36], the influence of the individual TEs in the genetic and epigenetic constitution of the host genomes [39] (Box 2), and drought stress [34]. Such studies illustrate ongoing intraspecific evolution of this Brachypodium species and how shifts in biodiversity could show the impact of environmental change.…”
Section: Trends Trends In In Plant Plant Science Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…21 out of the 25 most strongly upregulated genes did not cluster with other genes in the drought co-expression network (i.e., they were members of the grey D0 module), while the majority of these strongly upregulated genes did cluster in a module in the water network (Table S7). The 25 most strongly upregulated genes by drought showed a range of predicted functions which included two predicted dehydrins (Decena et al 2021), two ABA-associated proteins, and two lipid transfer proteins (LTPs) (Table S7). LTPs were among the most highly induced transcripts in an Arabidopsis thaliana experiment that imposed very similar soil drying conditions to those imposed in the present study (Des Marais et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In some species, it can convert caffeine-CoA into caffeic acid, but there are no orthologs in the genomes of B. distachyon, Z. mays and S. bicolor [48]. Devi et al showed that this diversity underscores the necessity to comprehend monolignol biosynthetic pathways in all lignocellulose cultures [21].…”
Section: Study Of the Miscanthus Genomementioning
confidence: 99%